Effects of short-term air pollution on aerobic performance and forced vital capacity (FVC): An experimental analysis - Safei, Imam; Pambudi, Yudhi Teguh; Resmana, Dadan (Journal Sport Area, 2024)
Background Problem: Nutrition plays an important role in fitness, yet there is limited understanding of how non-sporting students, particularly nutrition students, manage their fitness. This study fills the gap by exploring the relationship between physical activity, dietary habits, and fitness in this group. Research Objective: This study aims to examine the fitness profile of female undergraduate nutrition students and explore the factors associated with fitness such as physical activity level (PAL), nutritional status, and diet. Methods: To answer the research objective, a cross-sectional design was conducted, involving 114 healthy female students, aged 18-20 years old. Respondents were selected by using proportional random sampling, which enabled equal representation of each class in the study. Exclusion criteria: students have chronic disease or condition affecting physical fitness. Physical fitness was assessed using the Harvard Step Test, PAL was measured via an online self-administered IPAQ, nutritional status was assessed using a body mass index (BMI) calculation, and dietary data (energy and iron intakes) was assessed using 2x24 non-consecutive food records. Chi-squares or Fisher Exact tests were done to analyse the association between physical fitness and other variables. Finding and Result: We found that almost all of our respondents were at poor levels of physical fitness. There was no significant association between physical fitness and other variables such as PAL, BMI, and diet. Conclusion: This research supported previous findings that college students in health majors have poor fitness. Future studies should explore additional factors such as physiological stress, sleep pattern, or socio-economic status that may impact the fitness level of health-major students.